Differences in Sensory Characteristics and Aroma Compounds between Young and Aged Qingxiangxing Baijiu - SUN Xizhen, XIONG Yaqing, LIU Jiahuan, QIAN Quanquan, XIE Qianqian, WEI Shuxia, CHEN Yanhe (Shipin Kexue, 2023)
The characteristic aroma compounds of qingxiangxing baijiu were analyzed and the differences in sensory characteristics and aroma compounds between young and aged baijiu were clarified by sensory evaluation and techniques for qualitative and quantitative analysis of aroma compounds. Totally 69 odor-active compounds with flavor dilution (FD) factor ≥ 2 were confirmed by comparative aroma extract dilution analysis (CAEDA). A total of 40 odor-active compounds in young qingxiangxing baijiu and 43 in aged qingxiangxing baijiu were identified based on odor activity value (OAV). The important aroma compounds of young and aged baijiu were verified by aroma recombination experiments. Finally, heatmap analysis showed that the differential important aroma compounds (P ≤ 0.05) between young and aged qingxiangxing baijiu mainly included γ-butyrolactone, ethyl isovalerate, γ-nonanolactone, ethyl isobutyrate, 3-methylbutanoic acid, 1,1-diethoxyethane, β-phenylethanol, 2-pentyl furan, acetaldehyde, butanoic acid, ethyl hexanoate, benzaldehyde, furfural, vanillin, hexanal, 3-hydroxy-2-butanone, and 2,3-butanedione. In summary, microconstituents were more abundant in aged than young baijiu, and so were most esters, organic acids, aldehydes, and ketones, while the opposite was found for propanol, isobutanol, and 3-methylbutanol. These could be the major reasons for the significant differences in the sensory characteristics of young and aged baijiu.